Online support-provision in the self-disclosure of eating disorders - Zulkarnain, Nur Azwin; Jan, Jariah Mohd; Wahid, Ridwan (Indonesian Journal of Applied Linguistics, 2021)
This paper highlights the importance of appropriate communication with individuals who suffer from eating disorders (ED). The negative perception that society has towards ED often leads its patients to conceal their problems and avoid seeking help (Perveen et al., 2017). Understanding the manners in which support-providers approach ED patients in order to eliminate the fear is therefore important. Data was collected from the National Eating Disorders Association (NEDA) website from January to March 2018, where support-providers’ responses to posts of self-disclosure were qualitatively analyzed through computer-mediated discourse analysis (CMDA) using McCormack’s (2010) Categories of Social Support and Blum-Kulka and Olshtain’s (1984) Cross-Cultural Study of Speech Act Realization Patterns (CCSARP). Drawing on the categories of social support proposed by McCormack, it was found that most of the strategies that the support-providers opted for were highly positive and indirect in nature. The findings also showed that the indirect support given was often complemented with words of encouragement and a number of suggestions that were offered as part of the support itself. This allowed the support-providers to appear unimposing on the ED patients while being able to ensure that they were guided on the possible means of recovery.